Melt Growth and Physical Properties of Bulk LaInO3 Single Crystals. Issue 16 (17th July 2021) - Galazka, Zbigniew; Irmscher, Klaus; Ganschow, Steffen; Zupancic, Martina; Aggoune, Wahib; Draxl, Claudia; Albrecht, Martin; Klimm, Detlef; Kwasniewski, Albert; Schulz, Tobias; Pietsch, Mike; Dittmar, Andrea; et al.
Abstract : Large bulk LaInO3 single crystals are grown from the melt contained within iridium crucibles by the vertical gradient freeze (VGF) method. The obtained crystals are undoped or intentionally doped with Ba or Ce, and enabled wafer fabrication of size 10 × 10 mm 2 . High melting point of LaInO3 (≈1880 °C) and thermal instability at high temperatures require specific conditions for bulk crystal growth. The crystals do not undergo any phase transition up to 1300 °C, above which a noticeable thermal decomposition takes place. The good structural quality of the crystals makes them suitable for epitaxy. The onset of strong optical absorption shows orientation‐dependent behavior due to the orthorhombic symmetry of the LaInO3 crystals. Assuming direct transitions, optical bandgaps of 4.35 and 4.39 eV are obtained for polarizations along the [010] and the [100], [001] crystallographic directions, respectively. There is an additional weak absorption in the range between 2.8 and 4 eV due to oxygen vacancies. Density‐functional‐theory calculations support the interpretation of the optical absorption data. Cathodoluminescence spectra show a broad, structured emission band peaking at ≈2.2 eV. All bulk crystals are electrically insulating. The relative static dielectric constant is determined at a value of 24.6 along the [001] direction. Abstract : Large LaInO3 single crystals are grown from the melt by the vertical gradient freeze method. The obtained crystals are either undoped or intentionally doped with Ba or Ce and enable wafer fabrication of size 10 × 10 mm 2 . The structural quality, thermal stability, and physical properties of the obtained crystals are evaluated.